"Global Crises, Global Solutions /" - "Lomborg, Bj???rn" (Cambridge)
Includes bibliographical references.
Keywords: INTERNATIONAL COOPERATION.;GLOBALIZATION.;ECONOMIC DEVELOPMENT.;ECONOMIC POLICY.;ECONOMIC DEVELOPMENT -- ENVIRONMENTAL ASPECTS